Morphological features of the epididymal epithelium of gerbil, Meriones unguiculatus - Domeniconi, Raquel Fantin; Orsi, Antonio Marcos; Beu, Celia Cristina Leme; Felisbino, Sergio Luis (Churchill Livingstone, 2007)
Principal cells of the ducts epididymis of the Mongolian gerbil showed ultrastructural characteristics of lining epithelium cells close related to processes of protein secretion, and transcytosis occurring between adjacent principal cells which were mainly verified in the initial segment. Principal cells also presented roles of fluid phase and adsorptive endocytoses, as well as autophagic and heterophagic lysosomal activities mainly observed in the caput epididymis. Columnar (principal) cells of the corpus epididymidis presented great number of variable vesicles and vacuoles distributed in all the cytoplasmic levels occurring a progressive coalescence pattern among them, which help to guarantee formation of cytoplasmic channels for fluid phase transport between the tubular lumen and epididymal interstitium. Clear cells were presented in the initial segment and predominately in the cauda epididymis epithelium of the gerbil and showed marked ultrastructural characteristics of endocytosis activities occurrence, perhaps directly related to the turnover of fluid phase of spermatozoa stored into the lumen of the distal tail. Other epididymal epithelium cells were verified and described such as basal, halo, apical and dark cells, but they did not presented special ultrastructural features. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: epididymis; lining epithelium; morphology; morphometry; mongolian gerbil